2018
DOI: 10.1089/jpm.2017.0585
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of a Modified Mohs Paste Mixed with Zinc Oxide 10% Topical Oil-Based Ointment

Abstract: This study of a mixture of MP and Zn showed that the viscosity of mMP could be adjusted with glycerin. Also, the tissue fixation of mMP progressed slowly compared with that of MP. This finding suggests that mMP is effective and safe for Mohs treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Tsuruta et al reported a mixture of Mohs' paste and zinc oxide 10% single ointment, which showed that the viscosity of modified Mohs' paste could be adjusted with glycerin. 7 The effect of prescription improvement of the Mohs' paste on the pharmacological effect was examined with reference to water absorbing property, and its tumor tissue invasion fixation depth as an indicator. 8 In the modified Mohs' technique, invasion fixation depth increased depending on application time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuruta et al reported a mixture of Mohs' paste and zinc oxide 10% single ointment, which showed that the viscosity of modified Mohs' paste could be adjusted with glycerin. 7 The effect of prescription improvement of the Mohs' paste on the pharmacological effect was examined with reference to water absorbing property, and its tumor tissue invasion fixation depth as an indicator. 8 In the modified Mohs' technique, invasion fixation depth increased depending on application time.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the modified Mohs' technique, invasion fixation depth increased depending on application time. 7 The intended purpose of Mohs' paste application is to determine the appropriate use interval and contact time. The original Mohs' chemosurgery used a contact time of 24 hours for the purpose of removing the tumor.…”
Section: Discussionmentioning
confidence: 99%